Solar panel cleaning system - khan, Imran; J. , Mohana (International Journal of Psychosocial Rehabilitation, 2020)
A large amount of power was consuming in day-to-day life. The power is produced in different ways. Now a days, the main source to produce power is by using solar panels. These solar panels convert solar energy to electrical energy, which is consumed in daily life. A big decline in power generation by the collection of dust and dirt in the cells is the biggest problem facing the photovoltaic power. This impact has been important in countries where heat waves or poisonous ecosystems like desert areas and large cities are evident. The daily maintenance of the solar cells is needed in order to keep the solar panels operating at negligible power capacity. Human handling of the frames is not necessary for wider photovoltaic systems. In tough and turbulent situations in particular, or in winter conditions. This chapter gives a design for a customized low-level solar cell cleaning device. A controller is a PV solar panel dedicated to solutions for cleaning. By cleaning the dust on the solar panels, it produces power efficiently.